The caracal, Felis caracal caracal Schreber, 1776, as predator in the West Coast National Park - Avenant, Nico Loubser (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.